Integrating Smart Production Systems in the Era of Industry 5.0: Redefining Operational Efficiency and Human–Machine Collaboration - Mia Kusmiati (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
This research investigates the integration of Smart Production Systems (SPS) within the framework of Industry 5.0, emphasizing how such integration redefines operational efficiency and human–machine collaboration. The study aims to identify the contributions of smart technologies to productivity, sustainability, and human value in modern production systems. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines, drawing from international databases including Elsevier, Springer, IEEE Xplore, Wiley, Taylor & Francis, ACM, and SAGE, as well as national sources. Publications from 2023–2025 were screened using keywords such as “Industry 5.0,” “Smart Production Systems,” “Human–Machine Collaboration,” and “Operational Efficiency.” Thematic analysis categorized findings into four dimensions: operational efficiency, human–machine collaboration, industrial sustainability, and socio-ethical aspects. Results indicate that SPS integration significantly enhances operational efficiency while fostering adaptive and creative collaboration between humans and machines. The combination of Artificial Intelligence (AI), Cyber-Physical Systems (CPS), and human creativity establishes a resilient, sustainable, and innovative production paradigm. Successful implementation of Industry 5.0 requires harmonizing technological advancement, human skills, and ethical principles. Practically, the study offers insights for industry stakeholders and policymakers in designing human-centered digital transformation strategies, strengthening supply chain resilience, workplace safety, and innovation. This research contributes conceptually by highlighting ethical and sustainable human–machine interactions in future production systems.